Education on Knowledge and Attitudes About Smoking Behavior in Young Men in Junior High Schools - Dian Rezki Wijaya; Darwin, Nurul Khaerah; Farhansyah, Muhammad; Thalib, Mutiara; Laelah, Nur (Sociality: Journal of Public Health Service, 2024)
Tobacco is a threat to the health of people in the world, around 8 million people die from tobacco. Every year, more than 7 million people die due to direct tobacco consumption and around 1.2 million people die due to passive smoking and exposure to tobacco smoke. The aim of this service is to increase the level of knowledge and attitudes of young men regarding smoking behavior in junior high schools. The method used was the lecture method and providing posters containing smoking behavior. The target of this activity is 30 young men from SMPN 3 Gowa Regency. The results of the service show that there has been an increase in the level of knowledge and attitudes of students regarding smoking behavior. It is hoped that the school will have educational programs such as seminars where students participate actively to exchange opinions or ask directly about smoking behavior. Apart from that, carry out an anti-smoking campaign in the school environment, put up posters about smoking behavior and involve the role of parents in supervising students.